2014
DOI: 10.1371/journal.pone.0108752
|View full text |Cite
|
Sign up to set email alerts
|

Dental Follicle Cells Rescue the Regenerative Capacity of Periodontal Ligament Stem Cells in an Inflammatory Microenvironment

Abstract: AimsPeriodontal ligament stem cells (PDLSCs) are one of the best candidates for periodontal regeneration. Their function could be impaired in periodontitis microenvironment. Dental follicle cells (DFCs), serving as precursor cells and mesenchymal stem cells, have intimate connection with PDLSCs. However, it is still unknown whether DFCs could provide a favorable microenvironment to improve the proliferation and differentiation capacity of PDLSCs from healthy subjects (HPDLSCs) and patients diagnosed with perio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(48 citation statements)
references
References 40 publications
1
46
0
1
Order By: Relevance
“…PPDLSCs were harvested from periodontitis tissues when the periodontitis was in a static phase. Although the PPDLSCs were separated from the inflammatory microenvironment, the functional deficit could not be recovered during ex vivo culture and expansion, according to our current findings and previous studies by our group [16, 29]. Because the periodontitis was chronic in the patients, and the condition was persistent for a long time, we assumed that epigenetic modification could play a critical role in maintaining the functional deficit [30, 31].…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…PPDLSCs were harvested from periodontitis tissues when the periodontitis was in a static phase. Although the PPDLSCs were separated from the inflammatory microenvironment, the functional deficit could not be recovered during ex vivo culture and expansion, according to our current findings and previous studies by our group [16, 29]. Because the periodontitis was chronic in the patients, and the condition was persistent for a long time, we assumed that epigenetic modification could play a critical role in maintaining the functional deficit [30, 31].…”
Section: Discussionmentioning
confidence: 58%
“…Our group previously confirmed that the biological characteristics of PDLSCs are affected by extracellular microenvironment such as inflammation [9, 16] and aging [17, 18]. In the periodontitis microenvironment, the proliferation capability of PDLSCs obtained from patients diagnosed with periodontitis (PPDLSCs) is increased, but the osteogenic and adipogenic potentials are decreased, which induces unfavorable periodontal regeneration.…”
Section: Introductionmentioning
confidence: 73%
See 1 more Smart Citation
“…In an inflammatory environment, phosphorylated GSK-3β regulates the expression of TNF-α through the wnt pathway to suppress osteogenic differentiation of PDLSCs. 38 Here, we further demonstrated that suppressing GSK-3β activity regulated the expres-…”
Section: Discussionmentioning
confidence: 60%
“…Concerning this issue, Liu J et al, found that the function of PPDLSCs could be damaged in the periodontitis microenvironment. DFCs appeared to enhance the self-renewal and multi-differentiation capacity of both HPDLSCs and PPDLSCs, which indicates that DFCs could provide a beneficial microenvironment for periodontal regeneration using PdSCs [49].…”
Section: Recent Findings Regarding Pdscsmentioning
confidence: 88%